2004
DOI: 10.1096/fj.03-1053fje
|View full text |Cite
|
Sign up to set email alerts
|

RAGE‐ and TGF‐ β receptor‐mediated signals converge on STAT5 and p21wafto control cell‐cycle progression of mesangial cells: a possible role in the development and progression of diabetic nephropathy

Abstract: The molecular events associated with acute and chronic exposure of mesangial cells (MC) to hyperglycemia were evaluated. We found that, unlike high glucose (HG) and Amadori adducts, advanced glycation end products (AGE) and transforming growth factor-beta (TGF-beta) induced p21waf expression and accumulation of MC in G0/G1. TGF-beta1 blockade inhibited AGE-mediated collagen production but only partially affected AGE-induced p21waf expression and cell-cycle events, indicating that AGE by binding to AGE receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
43
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 55 publications
3
43
0
1
Order By: Relevance
“…In Table 1 we show that following 48 or 72 h of stimulation with ox-LDL, the proportion of cells in the S phase was increased. Conversely, as reported previously (33), AGE failed to induce cell cycle progression. A dose-response curve (from 10 to 100 g/ml ox-LDL) indicated that ox-LDL concentrations above 60 g/ml led to apoptosis.…”
Section: Resultssupporting
confidence: 80%
“…In Table 1 we show that following 48 or 72 h of stimulation with ox-LDL, the proportion of cells in the S phase was increased. Conversely, as reported previously (33), AGE failed to induce cell cycle progression. A dose-response curve (from 10 to 100 g/ml ox-LDL) indicated that ox-LDL concentrations above 60 g/ml led to apoptosis.…”
Section: Resultssupporting
confidence: 80%
“…Muscle sections were processed for immunofluorescence assays and immunohistochemistry analyses as previously described (29). A quantification of cells that expressed the indicated markers was obtained as previously described (30). Images were acquired using a Zeiss LSM 5 Pascal confocal laser-scanning microscope (Carl Zeiss, Jena, Germany) (19).…”
Section: Histological Immunofluorescence and Immunohistochemistry Amentioning
confidence: 99%
“…20 The mechanism is unknown and may involve receptors that can be activated by anionic ligands. 10,21 Thus, we propose that increased negative charge because of increased CML content in glycated collagen IV results in inhibition of mesangial cell proliferation. Blocking CML formation using PM diminished the negative charge of glycated collagen and protected cell proliferation.…”
mentioning
confidence: 93%
“…9 Circulating AGE-albumin also causes mesangial cell damage by affecting cell growth and collagen expression. 10 However, the cellular effects of ECM modifications may be different from the direct cellular toxicity of glucose, reactive carbonyl species, or circulating glycated albumin. Moreover, because these modifications accumulate on long-lived ECM proteins such as collagen IV, their effects would continue long after the levels of glucose and other cir-culating pathogenic factors are normalized.…”
mentioning
confidence: 99%